Riders on the wind - Swinburne, Laurence; Hubrich, Dan. (Milwaukee : Raintree Publishers, 1980)
An account of how three men in a hot air balloon trace Charles Lindbergh's solo airplane route across the Atlantic in 1978.
Keywords: Balloon ascensions -- Juvenile literature; Transatlantic flights -- Juvenile literature; Balloon ascensions; Transatlantic flights